A CLINICAL CASE OF ENDOVASCULAR TREATMENT OF POST-TRAUMATIC ANEURYSMS OF RENAL ARTERIES - Albert R. Gilemkhanov; Valentin N. Pavlov; Vladimir V. Plechev; Vladimir S. Ishmetov; T. R. Ibragimov; Rustam E. Abdrakhmanov; Sergey I. Blagodarov; Konstantin I. Zavialov; Valentin V. Kataev (Креативная хирургия и онкология)
Introduction. Aneurysm of renal artery is a rare and complex pathology of renal bloodstream. Large percentage of observations show that renal artery aneurysms are iatrogenic and happen due to urological interventions. Traumatic aneurysms are much less frequent. By the nature of the blood supply arterial aneurysms are subdiveded into those, which occur when the injured organ is only artery and arteriovenous aneurysms that occur while an artery is damaged along with the accompanying veins. Aneurysms may be treated only surgically, and the only exception is pregnancy. It is possible to use the open treatment option such as aneurysm resection with prosthetics, reanastomosing or its collateral plastics of the renal artery; exclusion of aneurysm with shunting of renal artery or its branches; resection of aneurysm with anastomosing of artery with azygos splanchnic arteries; complex reconstruction using autovein or internal iliac artery segment; including kidney resection at local infarction or nephrectomy in the case of evident nephrosclerosis.Materials and methods. This paper presents a clinical case of successful minimally invasive surgical treatment of traumatic aneurysm of renal artery. It was carried out through stenting of the right lowpolar renal artery: a coronary sheath was used to transfuse and implant the Explorer-Itgimedical Aneugraft 3.0 * 18.0 mm graft-system; the stent-graft was implanted into the right lowpolar renal artery so that it covers the aneurysm ostium. Results. The above case shows the possibility to successfully apply the endovascular method to treat posttraumatic aneurysms of renal arteries with derivative circulation.Conclusion. This technique can be safely and successfully used as an alternative to the traditional «open» surgery, as it is minimally invasive, and allows performing a complete blockade of the pathological blood flow and to avoid an additional operating trauma and compromenation of distal branches.